2009
DOI: 10.1016/j.brainres.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation of the spleen in male Brown Norway rats: A longitudinal aging study

Abstract: Aging leads to reduced cellular immunity with consequent increased rates of infectious disease, cancer and autoimmunity in the elderly. The sympathetic nervous system (SNS) modulates innate and adaptive immunity via innervation of lymphoid organs. In aged Fischer 344 (F344) rats, noradrenergic (NA) nerve density in secondary lymphoid organs declines, which may contribute to immunosenescence with aging. These studies suggest there is SNS involvement in age-induced immune dysregulation. Objectives The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Some previous reports 9 , 19 , 31 have shown that noradrenergic innervation is particularly rich in T-cell zones and in areas of mast cells/macrophages, whereas the follicular and nodular zones in which B cells mature, are poorly innervated. Scattered nerve fibers have been observed in the red pulp primarily associated with plexuses along the trabeculae.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some previous reports 9 , 19 , 31 have shown that noradrenergic innervation is particularly rich in T-cell zones and in areas of mast cells/macrophages, whereas the follicular and nodular zones in which B cells mature, are poorly innervated. Scattered nerve fibers have been observed in the red pulp primarily associated with plexuses along the trabeculae.…”
Section: Discussionmentioning
confidence: 85%
“… 9 , 10 , 15-20 Noradrenergic postganglionic nerve fibers enter the spleen with the splenic artery, run along the trabeculae in plexuses, extend into the white pulp along the central artery and end in the periarterial lymphatic sheath. 9 , 19 , 31 Additionally, some studies have provided evidence for existence of the parasympathetic innervation of the spleen. 9 However, the courses of the sympathetic nerves and parasympathetic nerves might be different.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with disc herniation were clearly younger than patients with LSS, and this might interfere with our results. However, during aging, nerve fiber density remains constant [44][45][46] or decreases, 47,48 but there are no data that demonstrate increased nerve fiber density during aging. From this point of view, the older LSS patients compared to the younger controls should have had a similar or a lower density of nerve fibers, but the opposite was found.…”
Section: Density Of Sensory and Sympathetic Nerve Fibers In The Ligammentioning
confidence: 99%
“…Given that there is an age-related drop in the plasma CA levels after decapitation stress [112] , the rise in the thymic NA level with age [55-57, 60, 61] cannot be ascribed to the changes in circulating CA levels. However, Bellinger et al [113] found that the density of noradrenergic nerve fibers progressively rises with age in thymi of Fisher 344 rats, so it was profoundly increased in middleaged compared with young adult animals.…”
Section: Age-related Changes In Thymic Ca Concentrationmentioning
confidence: 99%